Class ensemble for lower primaries ([s.n.])
The little marionettesnRing around a RosynLavenders bluenFox and goosenIf I had wingsnMorning prayernHush, my babenBilly boynBrahm's cradle songnDeck the hallsnHobby horsenThe skylark